1997
DOI: 10.1143/jjap.36.523
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Scale Erasable Recording Using Atomic Force Microscope on Phase Change Media

Abstract: We have demonstrated a nanometer-scale recording technique using an atomic force microscope (AFM) with an amorphous GeSb2Te4 film as a phase change medium. Data are recorded by changing the local electric properties of the film using a conductive AFM probe. The conductance of the film can be increased by more than one hundred times by applying a pulse voltage between the probe and the film. The recorded data are read by detecting the change in the conductance using the probe. The smallest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…[21] Conductive marks in an insulating surrounding were written using an AFM. It was shown that a conductive mark could also be (once) erased by applying a low dc voltage (-1 V) to the tip, but for rewriting a higher voltage (3 V) was used.…”
Section: Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] Conductive marks in an insulating surrounding were written using an AFM. It was shown that a conductive mark could also be (once) erased by applying a low dc voltage (-1 V) to the tip, but for rewriting a higher voltage (3 V) was used.…”
Section: Communicationmentioning
confidence: 99%
“…Polarity-dependent resistance switching was not reported in Ref. [21] and information on cyclability and data retention was not presented. Only current images were shown, but no topographic images.…”
Section: Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…These probes are used to induce semipermanent, nanoscale changes in storage media to record the binary data. One approach involved using highly conductive tips, either in contact ͑using modified atomic force microscope tips͒ [1][2][3] or in close proximity ͑using scanning tunneling microscope tips͒ 1,4,5 to a phase-change medium to deliver a current that, through Joule heating, induces stable amorphous or crystalline phase transformations to record information. Using these techniques, it was shown that it is possible to record stable crystalline marks in an amorphous material with diameters less than 50 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Kado and Tohda [12,13] have reported reversible recording in amorphous GeSb 2 Te 4 films using an AFM with conducting cantilevers, and detect a drop of the electrical resistance of the films when exposed to electrical pulses of −4 V. Ueno and Gan et al studied the microstructure and morphology of recorded marks in micro area by TEM [14] and X-ray diffraction [15][16][17][18], but it is difficult to relocation the recorded marks due to its small size. Ishiyama [19] evaluated the size of phase-change bits by their frictional contrast and deemed it an effective resort for in situ phase-change observation.…”
Section: Introductionmentioning
confidence: 99%